Application of PBL Model Differentiated Learning to Improve Critical Thinking Skills in Work and Energy Materials in Junior High School - Melyani; Stepanus Sahala Sitompul; Syaiful B Arsyid (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
This study aims to test the effect of the application of the Problem Based Learning (PBL) learning model based on differentiated learning on the improvement of students' critical thinking skills in work and energy materials at SMP Negeri 2 Selakau Timur. This study uses a quantitative method with a pre-experimental experiment design, namely by using one pretest-posttest group. The results of the study show that the application of the PBL model based on differentiated learning is able to significantly improve students' critical thinking skills. The average score of the pretest students was 17.25, while after the implementation of PBL learning, the posttest score increased to 84.83. This increase is evident with an N-gain value of 0.81, which indicates a high category of improvement. In addition, the implementation of differentiated learning with the PBL model reached an average of 90-92%, indicating that the learning went well and as expected. Based on the results of this study, it can be concluded that differentiated learning with the PBL model is effective in improving students' critical thinking skills, especially in work and energy materials.